Identification of the Potential Key Long Non-coding RNAs in Aged Mice With Postoperative Cognitive Dysfunction - Li, Ming; Chen, Chan; Zhang, Weiyi; Gao, Rui; Wang, Qiao; Chen, Hai; Zhang, Shu; Mao, Xiaobo; Leblanc, Mathis; Behensky, Adam; Zhang, Zheng; Gan, Lu; et al. (Frontiers in Aging Neuroscience, 2019)
Postoperative cognitive decline (POCD) is a significant complication of surgery in elderly patients. Emerging researches showed that long noncoding RNA (lncRNA) may play a critical role in the pathogenesis of POCD. Here we aimed to identify potential key lncRNAs involved in the development of POCD. LncRNA and mRNA expression profiles in hippocampal tissues from POCD and control mice were analyzed by microarray assay. Gene ontology (GO) and KEGG pathway enrichment analyses were conducted to probe the functions of dysregulated genes. Then, important factors of the mainly affected biological processes were measured in the hippocampus. Correlated coding-noncoding co-expression (CNC) networks were constructed. Finally, the potential key pairs of lncRNA and target mRNA implicated in POCD were probed. Our results showed that a total of 868 differentially expressed lncRNAs and 690 expressed mRNAs were identified. GO and KEGG analyses indicated that the differentially expressed genes were mainly associated with inflammatory and apoptotic signaling pathways. Surgery-induced inflammatory cytokines and apoptosis were significantly increased in hippocampal tissues of aged mice. In CNC network analysis, we found that LncRNA uc009qbj.1 was negatively correlated with apoptosis-associated gene Vrk2 level. LncRNA ENSMUST00000174338 correlated positively with expression of the inflammation and apoptosis-associated gene Smad7. LncRNA NONMMUT00000123687 mediated gene expression by binding the inflammation-regulated transcription factor Meis2. Our results suggested that these potential key lncRNAs and mRNAs may play a vital role in the development of POCD through mediating neuronal inflammation or apoptosis.